Effect of Antisolvent Application Rate on Film Formation and Photovoltaic Performance of Methylammonium‐Free Perovskite Solar Cells - Qingzhi An (Wiley-VCH, 2021)
The poor stability of perovskite solar cells that are based on methylammonium (MA)‐containing compositions has triggered immense interest in the development of MA‐free alternatives such as the double‐cation mixed‐halide Cs x FA1–x Pb(I1–x  + Br x )3 composition (CsFA perovskites). Although efficient solar cells based on this composition have been reported, many aspects related to the film formation of CsFA perovskites remain unclear. Herein, the influence of the antisolvent application rate on the properties and device performance of MA‐free perovskite solar cells are investigated. It is found that when applied slowly, all six of the investigated antisolvents result in high‐quality films and devices reaching a maximum power conversion efficiency of 20.7%. However, fast application leads to incomplete film coverage, and consequently no functional solar cells, for three of these antisolvents. It is demonstrated that this is related to the inefficacy of these antisolvents in triggering the crystallization of the perovskite layer and a simple test is offered that can aid researchers to identify whether other antisolvents will favor fast or slow antisolvent application.